Pemanfaatan Telehealth dalam Peningkatan Derajat Kesehatan Anak dengan Asma - Khotimah, Khusnul; Nilasari, Putri (Universitas Fort De Kock Bukittinggi, 2021)
Background: Asthma is a condition in which the airways are narrowed due to hyperactivity to certain stimuli, which causes inflammation. Telehealth includes the use of phone calls, text messages, email, or online health portals that allow patients to communicate with healthcare providers. Method: Design using Literature Review, which is a study based on a summary of several studies related to the research topic that has been determined. Journals used through searches with databases from EBSCOhost, ProQuest and Clinical Key between 2017 and 2021. Results: Based on the journals collected, the use of Telehealth in children with Asthma is effective in increasing the level of adherence to treatment, reducing the frequency of hospitalization and reducing the frequency of not attending school. because of recurrence. Conclusions and Recommendations:Telehealth facilitate monitoring of children's conditions and control the level of child adherence to treatment, reduce recurrence rates so that the quality of life of children with asthma is better which then reduces mortality due to asthma. The author recommends that Telehealth can be implemented in Indonesia. Keywords: Telehealth, Asthma, Pediatric